Recognising the Cost of Purchased Goodwill - Allen, Christina; Krever, Richard (2020)
The nature of “goodwill” for tax purposes was an important issue in Australia long before the adoption of the Commonwealth income tax, with the relationship between goodwill and sales of business premises a central issue in colonial stamp duty assessments (and consequent litigation). Judicial precedents and doctrines were transferred into the income tax arena as a result of a provision in the first Commonwealth income tax law that allowed depreciation of goodwill associated with leasehold interests. Judicial views were subsequently refined when the nature of goodwill was considered in the context of small business concessions for gains on the disposal of goodwill and in an important case in which a vendor created a notional goodwill asset in the course of a financial arrangement. Importantly, since 1964, Australian taxpayers have not been able to depreciate the cost of any form of purchased wasting goodwill. The Australian tax position stands in contrast with that of the UK, Canada, the US and many other countries. This article reviews the concept of goodwill in Australian tax law and suggests allowance of depreciation of purchased goodwill would be a logical reform to make, contributing to better alignment of the law with benchmark income tax principles.